The effect of various drugs on the glucuronidation of zidovudine (azidothymidine; AZT) by human liver microsomes. - Sim, S M (1991)
1. Zidovudine (3'-azido-3'-deoxythymidine; AZT) is the drug of proven efficacy available for the treatment of patients with AIDS or ARC. It is eliminated mainly by hepatic glucuronidation. Therefore, interference with this metabolic pathway may lead to enhancement of AZT effect or to increased toxicity of the drug. We have examined the effect of a number of drugs which themselves undergo glucuronidation on AZT conjugation by human liver microsomes in vitro. 2. AZT glucuronidation followed Michaelis-Menten kinetics. The apparent Km and Vmax values (mean +/- s.d., n = 5), were 2.60 +/- 0.52 mM and 68.0 +/- 23.4 nmol h-1 mg-1, respectively, as determined from Eadie-Hofstee plots. 3. Dideoxyinosine, sulphanilamide and paracetamol were essentially non-inhibitory at concentrations up to 10 mM (4 times the concentration of AZT in the incubation). The most marked inhibitory effects were seen with indomethacin, naproxen, chloramphenicol, probenecid and ethinyloestradiol, with enzyme activity decreased by 97.7, 94.9, 88.7, 83.4% and 79.0%, respectively, at a concentration of 10 mM. Other compounds producing some inhibition of AZT conjugation were oxazepam, salicylic acid and acetylsalicylic acid. 4. Further studies are necessary to characterise the inhibition observed but the method described enables a screen of potentially important drug interactions to be carried out.